STEPPING TRAIL MAKING TEST IS ASSOCIATED WITH GLOBAL COGNITIVE FUNCTION: A CONCURRENT VALIDITY STUDY. (11th November 2018) - Osuka, Y; Kim, H; Kojima, N; Watanabe, Y; Inagaki, H; Awata, S; Shinkai, S
Abstract: Walking ability is associated with cognitive function; however, a novel performance test that assesses both cognitive function and walking is required to further confirm this association. We originally developed the Stepping Trail Making Test (S-TMT) that assessed walking ability, attention, and executive function. This study demonstrated its concurrent validity as a cognitive indicator by identifying the association between the S-TMT and global cognitive function in older adults. Cross-sectional analyses were conducted using data from 1, 248 older Japanese adults (77.5 ± 4.8 years: 506 males, 742 females). S-TMT was conducted by measuring the time taken to step on numbers from 1 to 16 that were randomly positioned on a mat (1 square meter), as quick as possible with accuracy. The Mini-Mental State Examination-Japanese (MMSE-J) was used to assess global cognitive function. To demonstrate concurrent validity of the S-TMT, univariate and multivariate analyses were performed to identify the association between the S-TMT time and MMSE-J score. Univariate analysis revealed a significant association of S-TMT time with MMSE-J score (ρ = -0.304, P <0.001). Multiple regression analysis adjusted for covariates revealed that S-TMT time was significantly associated with MMSE-J score (β = -0.357, P <0.001). Even after stratified by sex, the associations remained significant (men: β = -0.412, women: β = -0.278, P <0.001). Longer S-TMT time was significantly and independently associated with lower MMSE-J score. Thus, the S-TMT has concurrent validity as a cognitive indicator in older adults. A longitudinal study is required to identify whether the S-TMT has predictive validity for cognitive decline.